If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(t + 1) = 2(t + 5) Reorder the terms: 4(1 + t) = 2(t + 5) (1 * 4 + t * 4) = 2(t + 5) (4 + 4t) = 2(t + 5) Reorder the terms: 4 + 4t = 2(5 + t) 4 + 4t = (5 * 2 + t * 2) 4 + 4t = (10 + 2t) Solving 4 + 4t = 10 + 2t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-2t' to each side of the equation. 4 + 4t + -2t = 10 + 2t + -2t Combine like terms: 4t + -2t = 2t 4 + 2t = 10 + 2t + -2t Combine like terms: 2t + -2t = 0 4 + 2t = 10 + 0 4 + 2t = 10 Add '-4' to each side of the equation. 4 + -4 + 2t = 10 + -4 Combine like terms: 4 + -4 = 0 0 + 2t = 10 + -4 2t = 10 + -4 Combine like terms: 10 + -4 = 6 2t = 6 Divide each side by '2'. t = 3 Simplifying t = 3
| -21+25=m-8 | | 4(w+2)=6(w+1) | | (u-7)(u-7)=2u^2-6u+64 | | 8t+9=25 | | 5(x+6)=2(x+27) | | 18-30=6z | | 3a=5a+80 | | x+(-2)=-66 | | 12t-5=9t+14 | | 3(x-9)=13-x | | 112-4x=23x+16 | | -4m+2(6m+1)=23+m | | -108+x=-5x+42 | | 5x+x+(4x-16)=180 | | 2x+6=1.75x+6 | | 2x+6=12-7x | | x^2-8=7x | | 78-4x=2x+12 | | 5b+11-4b=56 | | -9p-5=93 | | e^2x=57 | | 6(5a-1)(3a+1)=0 | | 3t/5-6=t/12 | | 4(x-3)=x+3 | | (7+w)(2w+9)=0 | | 10b+9-3b=4 | | 10-8x=36-15x | | x-67=-10x+131 | | 10+2(x+2)=20 | | -7(n+7)=-9-2n | | s^2-3s=0 | | 9x^4-144x^2= |